2022
DOI: 10.1073/pnas.2210990119
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar inhibition of SARS-CoV-2 infection by an unmodified peptide targeting the prehairpin intermediate of the spike protein

Abstract: Variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) challenge currently available coronavirus disease 2019 vaccines and monoclonal antibody therapies through epitope change on the receptor binding domain of the viral spike glycoprotein. Hence, there is a specific urgent need for alternative antivirals that target processes less likely to be affected by mutation, such as the membrane fusion step of viral entry into the host cell. One such antiviral class includes peptide inhibitors, which b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
0
34
1
Order By: Relevance
“…So far, therapeutic strategies targeting the S2 fusion machinery mainly focused on the development of anti-fusogenic synthetic peptides mimicking the HR2 domain. Such peptides were shown to inhibit formation of the native HR1/HR2 six-helix coiled-coil hairpin complex, thus preventing viral fusion and infection by several human coronaviruses in situ, including MERS-CoV, SARS-CoV and SARS-CoV-2 [43][44][45] . Furthermore, intranasal injection of a synthetic lipopeptide derived from HR2 was found to protect ferrets against infection by SARS-CoV-2 46 .…”
Section: Discussionmentioning
confidence: 99%
“…So far, therapeutic strategies targeting the S2 fusion machinery mainly focused on the development of anti-fusogenic synthetic peptides mimicking the HR2 domain. Such peptides were shown to inhibit formation of the native HR1/HR2 six-helix coiled-coil hairpin complex, thus preventing viral fusion and infection by several human coronaviruses in situ, including MERS-CoV, SARS-CoV and SARS-CoV-2 [43][44][45] . Furthermore, intranasal injection of a synthetic lipopeptide derived from HR2 was found to protect ferrets against infection by SARS-CoV-2 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Although previously reported HR1-derived peptide inhibitors exhibit poor inhibitory activities, foldon-mediated trimerization of the C-terminus conferred a HR1-derived peptide with higher inhibitory activity against SARS-CoV-2, SARS-CoV-2 variants of concern (VOCs), SARS-CoV, and MERS-CoV ( Bi et al, 2022 ). Moreover, an inspirational work identified that the extended N-terminus of HR2 also involves in interacting with HR1, and a synthetic peptide including this region achieved single-digit nanomolar inhibition of several SARS-CoV-2 variants ( Yang et al, 2022 ).…”
Section: Peptides Working At Different Infection Stages Are Potent An...mentioning
confidence: 99%
“…Compared to the conventional small molecule drugs, peptide synthesis can be quickly launched and modified ( Vagner et al, 2008 ; Gao et al, 2018 ). More importantly, the chemical composition makes peptides highly specific and effective to their targets, even at nanomolar or picomolar concentrations ( Cao et al, 2020 ; Schütz et al, 2020 ; Heydari et al, 2021 ; Shah et al, 2022 ; Yang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…He then presented his inspiring latest research using large scale data visualization to achieve automated recognition of organelles from FIB-SEM data for both cultured cells and tissue using deep learning-aided image processing . The final part of his presentation was dedicated to his contribution to the research on SARS-CoV-2, where his laboratory characterized the infection route for the virus and helped discover a simple peptide exhibiting highly inhibitory properties against infections against SARS-CoV-2 variants to date …”
mentioning
confidence: 99%
“…26 The final part of his presentation was dedicated to his contribution to the research on SARS-CoV-2, where his laboratory characterized the infection route for the virus 27 and helped discover a simple peptide exhibiting highly inhibitory properties against infections against SARS-CoV-2 variants to date. 28 After a restoring lunch break, the afternoon program was started by Prof. Paola Picotti (ETH Zurich, Switzerland), who shared her lab's latest results in revolutionizing proteomics to bring structural proteome snapshots into functional proteomics screens. Limited proteolysis-mass spectrometry (LiP-MS) not only allows the detection of small molecule binding to proteins through induced conformational changes but can also provide information on protein−protein binding or protein−metabolite interactions.…”
mentioning
confidence: 99%